Epilactose as a promising butyrate-promoter prebiotic via microbiota modulation - Cardoso, Beatriz B. (2024)
Epilactose is a disaccharide composed of galactose and mannose, and it is currently considered an under development prebiotic. In this study, we described the prebiotic potential of epilactose by in vitro fermentation using human fecal inocula from individuals following a Mediterranean diet (DM) or a Vegan diet (DV). The prebiotic effect of epilactose was also compared with lactulose and raffinose, and interesting correlations were established between metabolites and microbiota modulation. The production of several metabolites (lactate, short-chain fatty acids, and gases) confirmed the prebiotic properties of epilactose. For both donors, the microbiota analysis showed that epilactose significantly stimulated the butyrate-producing bacteria, suggesting that its prebiotic effect could be independent of the donor diet. Butyrate is one of the current golden metabolites due to its benefits for the gut and systemic health. In the presence of epilactose, the production of butyrate was 70- and 63-fold higher for the DM donor, when compared to lactulose and raffinose, respectively. For the DV donor, an increase of 29- and 89-fold in the butyrate production was obtained when compared to lactulose and raffinose, respectively. In conclusion, this study suggests that epilactose holds potential functional properties for human health, especially towards the modulation of butyrate-producing strains.